Digital health professions education in the field of pediatrics : systematic review and meta-analysis by the Digital Health Education Collaboration - Brusamento, Serena (2020)
Background: Reducing childhood morbidity and mortality is challenging, particularly in countries with a shortage of qualified health care workers. Lack of trainers makes it difficult to provide the necessary continuing education in pediatrics for postregistration health professionals. Digital education, teaching and learning by means of digital technologies, has the potential to deliver medical education to a large audience while limiting the number of trainers needed. Objective: The goal of the research was to evaluate whether digital education can replace traditional learning to improve postregistration health professionals’ knowledge, skills, attitudes, and satisfaction and foster behavior change in the field of pediatrics. Methods: We completed a systematic review of the literature by following the Cochrane methodology. We searched 7 major electronic databases for articles published from January 1990 to August 2017. No language restrictions were applied. We independently selected studies, extracted data, and assessed risk of bias, and pairs of authors compared information. We contacted authors of studies for additional information if necessary. All pooled analyses were based on random effects models. We included individually or cluster randomized controlled trials that compared digital education with traditional learning, no intervention, or other forms of digital education. We assessed the quality of evidence using the Grading of Recommendations, Assessment, Development, and Evaluations (GRADE) criteria. Results: Twenty studies (1382 participants) were included. Participants included pediatricians, physicians, nurses, and midwives. Digital education technologies were assessed including high-fidelity mannequins (6 studies), computer-based education (12 studies), mobile learning (1 study), and virtual reality (1 study). Most studies reported that digital education was either as effective as or more effective than the control intervention for outcomes including skill, knowledge, attitude, and satisfaction. High-fidelity mannequins were associated with higher postintervention skill scores compared with low-fidelity mannequins (standardized mean difference 0.62; 95% CI 0.17-1.06; moderate effect size, low-quality evidence). One study reported physician change in practicing behavior and found similar effects between offline plus online digital education and no intervention. The only study that assessed impact on patient outcome found no difference between intervention and control groups. None of the included studies reported adverse or untoward effects or economic outcomes of the digital education interventions. The risk of bias was mainly unclear or high. The quality of evidence was low due to study inconsistencies, limitations, or imprecision across the studies. Conclusions: Digital education for postregistration health professions education in pediatrics is at least as effective as traditional learning and more effective than no learning. High-fidelity mannequins were found to be more effective at improving skills than traditional learning with low-fidelity mannequins. Computer-based offline/online digital education was better than no intervention for knowledge and skill outcomes and as good as traditional face-to-face learning. This review highlights evidence gaps calling for more methodologically rigorous randomized controlled trials on the topic.